2011
DOI: 10.1002/ajpa.21495
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor behavior of wild orangutans (pongo pygmaeus wurmbii) in disturbed peat swamp forest, Sabangau, Central Kalimantan, Indonesia

Abstract: This study examined the locomotor behavior of wild Bornean orangutans (P. p. wurmbii) in an area of disturbed peat swamp forest (Sabangau Catchment, Indonesia) in relation to the height in the canopy, age-sex class, behavior (feeding or traveling), and the number of supports used to bear body mass. Backward elimination log-linear modeling was employed to expose the main influences on orangutan locomotion. Our results showed that the most important distinctions with regard to locomotion were between suspensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 44 publications
(106 reference statements)
1
50
0
Order By: Relevance
“…[2006] found that the nutritional value of the red-tailed monkey's (Cercopithecus ascanius) diet was significantly reduced in heavily logged forest, emphasising the implications that logging can have on animal health [Gillespie et al ., 2005]. When a forest is logged, the removal of large trees disrupts the upper canopy affecting travel routes and forcing arboreal species to descend to lower levels or even travel on the ground [Johns, 1986;Manduell et al, 2011]. This in turn can increase predation risks from terrestrial predators.…”
Section: Introductionmentioning
confidence: 99%
“…[2006] found that the nutritional value of the red-tailed monkey's (Cercopithecus ascanius) diet was significantly reduced in heavily logged forest, emphasising the implications that logging can have on animal health [Gillespie et al ., 2005]. When a forest is logged, the removal of large trees disrupts the upper canopy affecting travel routes and forcing arboreal species to descend to lower levels or even travel on the ground [Johns, 1986;Manduell et al, 2011]. This in turn can increase predation risks from terrestrial predators.…”
Section: Introductionmentioning
confidence: 99%
“…This runs counter to expectations of increased energy expended on travel being a potential cause of negative energy balance and possibly represents a statistical anomaly due to the relatively small sample size, with the accompanying interpretation that day range has no true influence on ketone production in flanged males in Sabangau. The absence of expected relationships here may also be related to potentially more energy efficient travel in the relatively continuous lower canopies of Sabangau, where the incidence of tree sway, identified as a highly energy efficient form of locomotion (Thorpe et al 2007), is much higher than in other habitat types studied to date (Manduell 2008). …”
Section: Discussionmentioning
confidence: 78%
“…Recent studies demonstrate that it is possible to obtain captures of primates with arboreal camera traps (Gregory et al, 2014) and cameras placed in carefully selected arboreal locations could supplement records on the ground. This might be especially useful in areas where there is a sex difference in use of the ground, as may be the case at certain locations in Wehea (e.g., sepans) and has been found at other orangutan study sites (e.g., Manduell et al, 2011). This technique, however, presents many hurdles (e.g., determining placement of cameras, the requirement of specialized expertise and equipment) and may also not be cost-effective in many areas.…”
Section: Tablementioning
confidence: 97%